KINERJA TURBIN GAS MIKRO BERBAHAN BAKAR LPG DENGAN VARIASI NILAI AIR FUEL RATIO (AFR) - Cahyani, Elisna Tirta; Ilminnafik, Nasrul; Kristianta, Fransiscus Xaverius (MEKANIKA: Jurnal Teknik Mesin, 2025)
The demand for electrical energy is expected to increase annually, making it necessary to reduce reliance on the main power grid. One solution is the use of micro gas turbines, which have a smaller power capacity and require fewer components compared to general gas turbines. In an experimental study, the impact of variations in air fuel ratio on the performance of micro gas turbines was investigated. The results showed that higher air fuel ratios led to an increase in the turbine's performance. The highest values recorded were 0.10 kJ/s for compressor work, 2.81 kJ/s for turbine work, 2.77 kJ/s for net work, 26.25 kJ/s for incoming heat, 8.54% for back work ratio, and 22.3% for thermal efficiency. This indicates that the air fuel ratio indeed influences the performance of micro gas turbines. Kata kunci: air fuel ratio, micro gas turbine, LPG fuel, micro gas turbine performance.